Analisis Faktor Pendukung Niat Perilaku terhadap Perilaku Penggunaan Layanan Paylater (Studi Kasus pada Karyawan di Institusi Keuangan Tahun 2023) - Rakhamawati, Diah; Suharto, Eduardus (BUDGETING : Journal of Business, Management and Accounting, 2024)
Digital developments in financial institutions create innovation in the products and services offered. The development of social media and the start-up industry, one of which is e-commerce, is quite popular among the public, therefore, many start-ups create pay-later products and services that are offered to the public. Ease of use, effectiveness in use, social influence and facilitating conditions are factors that influence a person's decision to use financial technology (fintech) services, especially paylater. This research aims to analyze how these factors influence the use of paylater services and how they influence the behavior of using paylater services through behavioral intentions. This research uses a quantitative approach with primary data whose correspondent objects are employees who work at financial institutions and the data will be processed and analyzed using SmartPLS. The results of this research explain that performance expectations, business expectations, social influences influence a person's intention to use paylater services, then facilitating conditions and usage intentions influence a person's behavior in using paylater services. Keywords: Behavioral Intentions, Fintech, Pay-later, Usage Behavior